The pedagogy of teaching English to young learners: Implications for teacher education - Subhan Zein (Indonesian JELT, 2017)
EYL (English for Young Learners) is a global phenomenon, and yet research is laden with reports suggesting teachers’ difficulty in developing appropriate EYL pedagogy (e.g. Butler, 2015; Copland, Garton & Burns 2014; Emery, 2012; Garton, Copland & Burns, 2011; Le & Do, 2012; Zein, 2015, 2016a, 2016b). This chapter reports on a study that investigated the perspectives of twenty-six (26) teachers on the appropriate pedagogy needed to teach in the EYL classroom. Data were collected through semi-structured interviews. The findings demonstrate that in the EYL classroom larger emphasis needs to be given to the young learners rather than the language. The findings show that developing a child-friendly pedagogy in the EYL classroom is of vital importance; it is at the core of EYL pedagogy. This brings implications for TESOL teacher education at pre-service and in-service levels in the sense that TESOL teacher educators need to design courses aimed to foster child-friendly pedagogy. The chapter specifically argues for TESOL teacher education to make stronger emphasis on child individual differences (IDs). This is necessary in order to equip teachers with appropriate working knowledge in second language acquisition (SLA) that is prerequisite to the development of EYL teaching expertise.